2013
DOI: 10.1093/mnras/sts514
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological simulations with self-interacting dark matter – I. Constant-density cores and substructure

Abstract: We use cosmological simulations to study the effects of self-interacting dark matter (SIDM) on the density profiles and substructure counts of dark matter halos from the scales of spiral galaxies to galaxy clusters, focusing explicitly on models with cross sections over dark matter particle mass σ/m = 1 and 0.1 cm 2 /g. Our simulations rely on a new SIDM N-body algorithm that is derived self-consistently from the Boltzmann equation and that reproduces analytic expectations in controlled numerical experiments. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
905
5
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 714 publications
(972 citation statements)
references
References 118 publications
45
905
5
4
Order By: Relevance
“…5. These systems have less dramatic differences between peak mass and current mass and their infall times are typically more recent (∼ 4-9 Gyr ago), consistent with previous studies of the likely infall times of different MW dSphs (Rocha et al 2013). Their gas content and SFR fall to zero more quickly after infall, around the first apocentre unless their orbit stays far from the galactic centre the whole time (e.g.…”
Section: Mass Evolutionsupporting
confidence: 88%
“…5. These systems have less dramatic differences between peak mass and current mass and their infall times are typically more recent (∼ 4-9 Gyr ago), consistent with previous studies of the likely infall times of different MW dSphs (Rocha et al 2013). Their gas content and SFR fall to zero more quickly after infall, around the first apocentre unless their orbit stays far from the galactic centre the whole time (e.g.…”
Section: Mass Evolutionsupporting
confidence: 88%
“…Indeed, Rocha et al (2013) find scatter in core sizes at given halo mass. Future studies will be able to quantify such scatter, and its mass dependence, which may result in a better match between the SIDM model and observations for smaller core sizes.…”
Section: Discussionmentioning
confidence: 98%
“…2014c) is the possibility that dark matter has a small, but not negligible, probability of interaction. Simulations have shown that this mechanism, if present, is able to flatten the cusps of cluster halos and on the necessary scales up to 100 kpc (Rocha et al 2013). In addition to the flattening, if DM interacts, it should exhibit a friction effect that could in principle be studied by possible shifts between the peaks of the DM distribution and the galaxies.…”
Section: Dark Matter Distributionmentioning
confidence: 99%